Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Di Biro Pelayanan Sosial Dasar Sekretariat Daerah Provinsi Jawa Barat - Astadi Pangarso; Putri Intan Susanti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
Bureau of Social Services in West Java Provinces has a fundamental duty organize formulation of general policy and coordination, reporting and evaluation of religion, education and culture, health and the environment. Employees have an important role in carrying out the task of the Bureau of Social Services. Implementation of discipline for employees has a function to improve employee performance. The Problems of this bureau is the declining performance of employees in 2015 due to lack of work discipline on Bureau of Social Services in West Java Regional. The effort to improve employee performance with these problems is suspected factors work discipline that has an influence on employee performance. Work discipline has a very high influence in the creation of employee performance Bureau of Social Services in West Java Regional, the value of R (correlation) produced is 0,745, it can be said that the discipline of work and employee performance are positively related 74.5% , While the coefficient of determination R2 (R Square) is 0.554, which means the ability to work discipline variable in influencing the performance of employees in the Bureau of Social Services in West Java Regional amounted to 55.4%, while 44.6% is the contribution of other factors which was not observed in this study. Employee performance (Y) can be explained by the discipline of work through regression Y = 0,646 + 0,849 X. This shows the influence of employee discipline (X) on employee performance (Y) is positive at 0,849, thus if the variable work discipline has increased 0,849 then the variable performance of employees will also increase number of 0,646.